RETELLING STORY WITH WAYANG IN TEACHING SPEAKING SKILL - Ramadani, Tri Kurniawati; RufinuS, Albert; Rosnija, Eni (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Â AbstractThe purpose of this research is to know whether Retelling Story with Wayang in teaching speaking skill is effective to the eighth grade students of SMP Negeri 01 Seluas in academic year 2015/2016. The method used was quasi experimental research. The subject of this research consisted of 33 students for experimental group and 33 students for the control group. In collecting the data, the researcher who teaches both of the group, prepared the worksheet, media, and speaking material. Then, the data of this research were taken from the measurement technique (pre-test and post-test) by using oral test. Based on the data analysis, the mean score of pre-test in experimental group was 38.91 and 42.82 for the control group. On the other hand, the mean score of post-test in experimental was 72.48 and 63.12 for control group. The mean score in experimental group represented high score than in control group. Through the t-test computation, t-value was higher than t-table (4.98>2.00) and the effect size of this treatment is 1.5 that means the treatment has strong effect. It indicated that Retelling Story with wayang was effective in Teaching Speaking Skill in terms of fluency, accuracy, and comprehension. Referring to the result, the Null Hypothesis (Ho) was rejected and thus the alternative hypothesis which saysâ€ Retelling Story with wayang is effective in Teaching Speaking Skill was accepted.Â Keyword: Effectiveness, Retelling Story, Wayang, Teaching SpeakingÂ Â